Can non-momentum factor premiums explain the momentum anomaly on the JSE? An in-depth portfolio attribution analysis. Issue 1 (2nd January 2019) - Page, Daniel; Auret, Christo
ABSTRACT: South African literature related to the momentum anomaly is generally limited to the exploration of momentum on a univariate and at most a bivariate basis, such as in combination with value (Fraser & Page, 2000) or liquidity (Page, Britten, & Auret, 2013). All of the literature thus far indicates that momentum is both present and significant on the cross-section of shares listed on the JSE, yet is narrow in that the current paradigm only considers raw or gross returns (on a univariate or bivariate basis) or risk-adjusted returns applying minimal factors as explanatory variables. This study intends to broaden the existing body of knowledge by applying numerous potential explanatory factors within a multifactor linear framework, utilising market proxies, size and value as independent variables. The key research question to be evaluated is whether various combinations of the independent variables considered are able to explain and provide insight into the dynamics of the momentum premium on the JSE. The findings of the study are largely consistent with the international literature, as none of the non-momentum factor premiums is able to explain the momentum premium.